Analisis Penerapan Syariah Compliance Terhadap Kepuasan Nasabah Studi Pada Bank Syariah Indonesia Kantor Cabang Stabat - Nurhaliza, Nurhaliza (Peduli Riset dan Pengabdian Masyarakat, 2022)
One of the important pillars in the development of Islamic financial institutions is sharia compliance. This pillar is the main difference between Islamic financial institutions and conventional financial institutions. This situation makes people want to know more about sharia compliance in Islamic banks. The objectives to be achieved in this research are to find out how the implementation of sharia compliance at Bank Syariah Indonesia KCP Stabat and to find out how customer satisfaction with sharia compliance at Bank Syariah Indonesia KCP Stabat. This study uses a qualitative descriptive research method. Data and information obtained by the author using the method of observation, interviews, and distributing questionnaires. The research population is all customers of Bank Syariah Indonesia KCP Stabat totaling 100 respondents. The results showed that to ensure the application of sharia compliance at Bank Syariah Indonesia KCP Stabat, the Bank held a reading discuss, comparative discussion between managerial, marketing and operational employees to avoid fraud, and the application of sharia compliance to the level of customer satisfaction at Bank Syariah Indonesia KCP Stabat. already in a satisfied position. This can be seen through the continuum line, the score obtained is 2,195 with a percentage score of 71.16% of the expected score of 2,520. The satisfied category means that Bank Syariah Indonesia KCP Stabat has implemented sharia compliance well.